Manajemen Program Kelas Tahfidz untuk Meningkatkan Kualitas Hafalan Al-Qur’an Siswa MTs Sabilul Muttaqin Pungging - Mar’atus Sholikhah; Affan Hasnan Mubarok; Khoirunnisak il fitriyah (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
This study aims to describe the management of the Tahfidz class program in improving students’ memorization quality at MTs Sabilul Muttaqin Pungging and to identify the supporting and inhibiting factors. The research focuses on three main aspects: (1) the implementation of the Tahfidz program, (2) the improvement of students’ memorization quality, and (3) the factors influencing the program. This study employed a qualitative approach with a descriptive method. Data were collected through direct observation of the program implementation, in-depth interviews with teachers and students, and analysis of related documents. The results show that the management of the Tahfidz class program at MTs Sabilul Muttaqin Pungging follows good program management principles through planning, implementation, and evaluation stages. The program has positively impacted students’ ability and interest in memorizing the Qur’an. Students demonstrated significant improvement in memorization accuracy and fluency, with fewer errors recorded by teachers. Supporting factors include qualified human resources, a conducive peer environment, and special Tahfidz classrooms, while inhibiting factors involve limited time, variation among teachers receiving memorization submissions, and the absence of a written curriculum.